A fully enclosed, 3D printed, hybridized nanogenerator with flexible flux concentrator for harvesting diverse human biomechanical energy. (November 2018) - Maharjan, Pukar; Cho, Hyunok; Rasel, M. Salauddin; Salauddin, Md.; Park, Jae Yeong
Abstract: Human body motion is highly regarded as a promising source of energy for powering body-worn electronic devices and health monitoring sensors. Transforming the human biomechanical energy into an electrical energy provides a sustainable energy to drive those devices and sensors, reducing their battery dependency. This work presents a fully-enclosed wrist-wearable hybridized electromagnetic-triboelectric nanogenerator (FEHN) for effectively scavenging energy from the low-frequency natural human wrist-motion (≤ 5 Hz). The FEHN incorporates the rolling electrostatic induction and electromagnetic induction using a freely moving magnetic ball inside a hollow circular tube. The materials used in 3D printing technology are used as energy harvesting material for easy, quick and worthwhile fabrication of the FEHN. A thin flexible flux concentrating material is introduced to increase the emf and enhances the electromagnetic output performance. The FEHN can harvest energy under the diverse circumstances and irregular wrist-motions, such as swinging, waving, shaking, etc. Following the experiments, the FEHN achieves an average power density of 0.118 mW cm −3 and can drive a commercial wrist-watch continuously for more than 23 min from just 5 s of wrist motion. This successful demonstration renders an effective approach for scavenging wasted biomechanical energy and provides a promising solution towards the development of sustainable power supply for wearable electronic devices and self-powered healthcare monitoring sensors. Graphical abstract: fx1 Highlights: A fully enclosed, 3D printed and hybridized nanogenerator, isolated from external environment is newly developed Sustainable nanogenerator for powering body-worn wearable electronic devices and healthcare monitoring sensors. Highly capable of harvesting energy from diverse wrist motions such as swinging, waving, shaking, twisting, etc. A flexible FeSiCr/PDMS composite based flux concentrator around the copper coil is applied to increase the induced emf. 5 s of wrist motion is enough to power a commercial electronic wrist-watch for more than 23 min continuously.